qanda-logo
apple logogoogle play logo

Calculator search results

Formula
Solve the quadratic equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
$$x ^ { 2 } + 2 x - 15 = 0$$
$\begin{array} {l} x = 3 \\ x = - 5 \end{array}$
Solve quadratic equations using the square root
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 15 } = \color{#FF6800}{ 0 }$
$ $ Convert the quadratic expression on the left side to a perfect square format $ $
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 15 } \color{#FF6800}{ - } \color{#FF6800}{ 1 } ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
$\left ( x + 1 \right ) ^ { 2 } \color{#FF6800}{ - } \color{#FF6800}{ 15 } \color{#FF6800}{ - } \color{#FF6800}{ 1 } ^ { \color{#FF6800}{ 2 } } = 0$
$ $ Move the constant to the right side and change the sign $ $
$\left ( x + 1 \right ) ^ { 2 } = \color{#FF6800}{ 15 } \color{#FF6800}{ + } \color{#FF6800}{ 1 } ^ { \color{#FF6800}{ 2 } }$
$\left ( x + 1 \right ) ^ { 2 } = 15 + \color{#FF6800}{ 1 } ^ { \color{#FF6800}{ 2 } }$
$ $ Calculate power $ $
$\left ( x + 1 \right ) ^ { 2 } = 15 + \color{#FF6800}{ 1 }$
$\left ( x + 1 \right ) ^ { 2 } = \color{#FF6800}{ 15 } \color{#FF6800}{ + } \color{#FF6800}{ 1 }$
$ $ Add $ 15 $ and $ 1$
$\left ( x + 1 \right ) ^ { 2 } = \color{#FF6800}{ 16 }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 16 }$
$ $ Solve quadratic equations using the square root $ $
$\color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \pm \sqrt{ \color{#FF6800}{ 16 } }$
$\color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \pm \sqrt{ \color{#FF6800}{ 16 } }$
$ $ Solve a solution to $ x$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ 4 } \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ 4 } \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
$ $ Separate the answer $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ + } \color{#FF6800}{ 4 } \\ \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ + } \color{#FF6800}{ 4 } \\ x = - 1 - 4 \end{array}$
$ $ Add $ - 1 $ and $ 4$
$\begin{array} {l} x = \color{#FF6800}{ 3 } \\ x = - 1 - 4 \end{array}$
$\begin{array} {l} x = 3 \\ x = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \end{array}$
$ $ Find the sum of the negative numbers $ $
$\begin{array} {l} x = 3 \\ x = \color{#FF6800}{ - } \color{#FF6800}{ 5 } \end{array}$
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple logogoogle play logo